In vitro assembly of virus-like particles of a gammaretrovirus, the murine leukemia virus XMRV - Hadravová, Romana; de Marco, Alex; Ulbrich, Pavel; Stokrová, Jitka; Dolezal, Michal; Pichová, Iva; Ruml, Tomás; Briggs, John A G; Rumlová, Michaela (Journal of virology, 2012)
Immature retroviral particles are assembled by self-association of the structural polyprotein precursor Gag. During maturation the Gag polyprotein is proteolytically cleaved, yielding mature structural proteins, matrix (MA), capsid (CA), and nucleocapsid (NC), that reassemble into a mature viral particle. Proteolytic cleavage causes the N terminus of CA to fold back to form a β-hairpin, anchored by an internal salt bridge between the N-terminal proline and the inner aspartate. Using an in vitro assembly system of capsid-nucleocapsid protein (CANC), we studied the formation of virus-like particles (VLP) of a gammaretrovirus, the xenotropic murine leukemia virus (MLV)-related virus (XMRV). We show here that, unlike other retroviruses, XMRV CA and CANC do not assemble tubular particles characteristic of mature assembly. The prevention of β-hairpin formation by the deletion of either the N-terminal proline or 10 initial amino acids enabled the assembly of ΔProCANC or Δ10CANC into immature-like spherical particles. Detailed three-dimensional (3D) structural analysis of these particles revealed that below a disordered N-terminal CA layer, the C terminus of CA assembles a typical immature lattice, which is linked by rod-like densities with the RNP.
Keywords: sekvence nukleotidů; DNA primery; sekvenční homologie aminokyselin; Proteolysis; Sequence Homology, Amino Acid; Molecular Sequence Data; Viral Proteins; molekulární sekvence - údaje; virion; Escherichia coli; Fourier Analysis; proteolýza; Amino Acid Sequence; virové proteiny; Base Sequence; sestavení viru; Leukemia Virus, Murine; Virion; Fourierova analýza; polymerázová řetězová reakce; DNA Primers; Polymerase Chain Reaction; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Virus Assembly; elektronová kryomikroskopie; virus myší leukemie; Cryoelectron Microscopy; sekvence aminokyselin